2019
DOI: 10.20429/ijsotl.2019.130308
|View full text |Cite
|
Sign up to set email alerts
|

‘Peer Critique’ in Debate: A Pedagogical Tool for Teaching Architectural Design Studio

Abstract: Post-digital architectural education aims to empower future architects by developing open-mindedness and technical skills for the design of non-standard spatial configurations. Students can learn through exploration and experimentation, using three-dimensional graphic design software to generate initial designs and quality feedback, with a mixed model of peers and panel judges assessing final projects. Ratings of individual contributions and performance are commonly found in literature on peer assessment, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 25 publications
(41 reference statements)
0
7
0
Order By: Relevance
“…Dunbar et al ( 2018 ) found that collaborative learning environments promote social self-efficacy, which in turn promotes academic performance. Peer interaction in the design studio contributes to a collaborative learning structure (Wang, 2010 ) so that students become proactive, self-regulating learners (Crolla et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Dunbar et al ( 2018 ) found that collaborative learning environments promote social self-efficacy, which in turn promotes academic performance. Peer interaction in the design studio contributes to a collaborative learning structure (Wang, 2010 ) so that students become proactive, self-regulating learners (Crolla et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we followed a convergent mixed-methods procedure (see Creswell & Plano Clark, 2018) undertaking quantitative and qualitative investigation concurrently. We integrated the results through merging analysis and interpreted them to gain a realistic and holistic understanding of students' strategy use.…”
Section: Methodsmentioning
confidence: 99%
“…Clearly et al (2012) highlight multifaceted evaluation as the most useful method for increasing self-regulation strategies knowledge (e.g., Baldan Babayigit & Guven, 2020;Coertjens et al, 2016;Foerst et al, 2017;Hendriks et al, 2020;Jansen et al, 2020;Pekrun et al, 2002;van Laer & Elen, 2020). Mixed methods approach offers advantages for SRL studies in compensating for missing data and confirming overlapping data (see Plano Clark, 2019). This study aimed to identify design students' SRL strategy use, taking advantage of both questionnaires and interviews as mixed methods.…”
Section: Self-regulated Learningmentioning
confidence: 99%
“…Other scholars of design‐related disciplines mention involvement of peers in the critique process, but primarily in the context of instructor guidance (Belluigi, 2016; Budge et al, 2013; Dannels & Martin, 2008; Healy, 2016). Similar research includes peer feedback, or peer critique, as a method and even suggests potential positive impacts associated with peer integration (Anthony, 1991; Crolla et al, 2019; Lawrence & Zollinger, 2015; Megahed, 2018; Oh et al, 2013; Utaberta et al, 2010). Smith (2011) specifically stated that “student‐led crits have been proven to facilitate higher‐order discussion than traditional ones” (p. 58).…”
Section: Review Of Literaturementioning
confidence: 99%